Социальная солидарность: развитие понятия в истории социологии и современные интерпретации - Урсуленко, К. (Социология: теория, методы, маркетинг, 2009)
The concept of social solidarity is one of the fundamental notions in classical social theory. The paper presents a study of this concept’s development in famous sociologist’ works (O.Compte, H.Spenser, F.Tönnies, E.Durkheim, K.Marx) as well as modern Ukrainian, Russian, European and American social scientists’ researches. The author develops a theoretical definition of the concept “social solidarity" by drawing on three approaches to the notion definition. These are attributes distinction, explanation of the functions and description of relationships between this concept and other concepts of social theory. As a conclusion, a general definition of “social solidarity" is presented, which is an important conceptual precondition for developing and usage of the concept in empirical studies.